Anti-idiotypic mimicry of a neutralizing epitope on the glycoprotein B complex of human cytomegalovirus. - Tackaberry, E S (1993)
Experiments were carried out to investigate the ability of rabbit anti-idiotype antibodies (Ab2), directed against an anti-human cytomegalovirus monoclonal antibody (Ab1), to induce neutralizing antibodies specific for the immunodominant glycoprotein B viral complex. Mice immunized with Ab2 produced anti-Ab2 (Ab3) that was both antigen and idiotype specific with regard to Ab1. We conclude that the Ab2 antibodies mimicked a neutralizing epitope and acted as a network antigen for inducing a specific anti-human cytomegalovirus antibody response in this experimental system.